Development of a new generation of quench and partitioning steels: Influence of processing parameters on texture, nanoindentation, and mechanical properties. (15th January 2020) - Ariza-Echeverri, E.A.; Masoumi, M.; Nishikawa, A.S.; Mesa, D.H.; Marquez-Rossy, A.E.; Tschiptschin, A.P.
Abstract: A novel quenching and partitioning process (Q&P) including the hot stamping (HS) process was studied, using two stamping temperatures (750 °C and 800 °C) and two quenching temperatures (318 °C and 328 °C). This combination is here called Hot Stamping and Quenching and Partitioning process (HSQ&P). The partitioning step was performed at 400 °C for 100 s in all cycles. Microstructural features were comprehensively studied using electron backscattered diffraction and nanoindentation techniques. HSQ&P samples showed a good combination of ductility and high-strength due to the presence of: retained austenite, inter-critical ferrite with low stored internal strain energy, grain refinement via DIFT-effect (deformation induced ferrite transformation), martensite, and bainite. Significant internal stress relief was caused by carbon partitioning, which was induced by the DIFT-effect and the partitioning stage. This also led to a considerable stored energy, which was characterized by the Kernel average dislocation and geometrically necessary dislocation analysis. In addition, predominant {110}//strain direction crystallographic texture was identified, which promotes slip deformation and enhances the mechanical properties. Moreover, remarkable amounts of fine film-like retained austenite oriented along compact crystallographic directions (i.e., 〈111〉 and 〈112〉) were observed. Finally, subsize tensile test verified the optimum mechanical behavior of HSQ&P specimens. Graphical abstract: Unlabelled Image Highlights: Hot stamping followed by Q&P process in TRIP-steels causes excellent combination of mechanical strength and elongation Combined nanoindentation and EBSD analysis is applied for phase identification and calculate localized mechanical properties Predominance of {110}//ND texture in retained austenite grains {111} and {112}//ND texture in BCC grains enhances efficiently the TRIP-effect.